AUTEKOLOGI PURNAJIWA (EUCHRESTA HORSFIELDII (LESCH.) BENN. (FABACEAE) DI SEBAGIAN KAWASAN HUTAN BUKIT TAPAK CAGAR ALAM BATUKAHU BALI - -, Sutomo; Mukaromah, Laily (Jurnal Biologi Udayana; Vol 14 No 1 (2010): Jurnal Biologi, 2010)
Purnajiwa, which lives in highland jungles in Bali, is a famous medicinal plant in Bali and its presence in the wild is now under threat due to over exploitation and the destruction of its habitat. Batukahu nature reserves are one of its remaining habitats. This preliminary study aimed to describe purnajiwa’s habitat in Batukahu nature reserves. Purnajiwa was found in shaded areas with light intensity range from 55-65%. It grows under the shading of Laportea sp., Ficus sp., Syzygium zollingerianum, and Sauraria sp. Purnajiwa grows on soil with 6,7-6,8 range of pH with litter thickness of 3-7 cm. Purnajiwa also associated with the surrounding understorey vegetation such as Diplazium proliferum (IVI = 54,6) and Oplismenus compositus L. (IVI = 40). Result from this study gave usefull information for the purpose of its acclimatization and propagation in ex-situ conservation for its sustainable resources.
Keywords: autekologi, purnajiwa, tapak hill, batukahu nature reserve